1992
DOI: 10.1159/000107011
|View full text |Cite
|
Sign up to set email alerts
|

On the Question of the Mental State of Centenarians

Abstract: The number of individuals over age 100 years in the United States will increase from 25,000 in 1986 to more than 108,000 by the year 2000. Despite this expected growth there is almost no information about their intellectual function. This is unfortunate since the study of centenarians offers valuable insight into the effects of aging upon the central nervous system. It may also clarify whether Alzheimer''s disease represents premature aging. To better understand their mental state, I evaluated 20 centenarians … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
(21 reference statements)
2
5
0
Order By: Relevance
“…‘Impaired wakefulness’ and ‘confusion’ were more severe and ‘waking up and wandering at night’ was also more frequent as the first episode in D90G than in LOG. Our results are probably compatible with those of Powell 7,8 . He suggested that common disturbed pattern of dementia in the oldest old age consisted of preserved awareness of environment, normal participation in conversations and memory impairment with diminished ability to acquire new information.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…‘Impaired wakefulness’ and ‘confusion’ were more severe and ‘waking up and wandering at night’ was also more frequent as the first episode in D90G than in LOG. Our results are probably compatible with those of Powell 7,8 . He suggested that common disturbed pattern of dementia in the oldest old age consisted of preserved awareness of environment, normal participation in conversations and memory impairment with diminished ability to acquire new information.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, AD could be regarded as an ‘age‐related’ rather than an ‘aging‐related’ disorder. In contrast, most of the subjects who survive over 100 are cognitively impaired or demented 7,8 , 11,14 . This indicates that aging might be considered another risk factor precipitating cognitive impairment and that dementia in the oldest old could be different from that of earlier onset.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, none of our subjects could be defined as demented according to DSM‐III‐R criteria, 12 but most of them had MMSE scores below the usual threshold for diagnosis of cognitive impairment. Data on the cognitive status of the oldest‐old' 21,22 confirm the paramount weight of schooling in MMSE performance pointed out previously in younger old cohorts 1 . Because education in our sample was generally of a very low level, many individuals who are actually free of dementia exhibit cognitive impairment using the usual MMSE cut‐off of 24/30.…”
Section: Discussionsupporting
confidence: 78%
“…Necessary clinical attributes for the diagnosis of probable DAT were absent in the majority of subjects in this study [17,22,23], Establishing the pres ence of apraxia is difficult since apraxia is excluded by motor disturbance that might interfere with testing.…”
Section: Discussionmentioning
confidence: 95%